The Rise of Singapore - Hong, Mark; Lugg, Amy (New Jersey : World Scientific, 2016)
'In the 50th anniversary year of Singapore's independence, it is timely to trace our developmental journey in order that young Singaporeans students, visiting tourists and foreigners working in Singapore may be informed about why and how Singapore succeeded, despite tremendous odds. The two volumes relate the developmental stories and secrets of Singapore, so that other developing countries can be inspired to achieve their own successes'--
volume 1. The reasons for Singapore's success - volume 2. Reflections on Singapore.
Includes bibliographical references.
Keywords: Singapore -- History -- 1965-1990.; Singapore -- History -- 1990-; Singapore -- Politics and government; Singapore -- Social conditions; Singapore -- Foreign relations